Influencer Marketing’s Effect on Purchasing Decisions in the Health and Fitness Industry from the Perspective of Millennial Consumers (International Journal of Food and Nutritional Sciences, 2022)
Influencer marketing has become a pivotal strategy in the health and fitness industry, particularly among millennial consumers. This study explores the impact of influencer marketing on purchasing decisions within this demographic in India. This study uses a crosssectional research design. The population for this study comprises millennial consumers in India who are active on social media and follow health and fitness influencers. Millennials are defined as individuals born between 1981 and 1996. A stratified random sampling technique was used to ensure representation across different age groups, genders and fitness levels. The sample size consisted of 90 Millennials who were surveyed using an online questionnaire in Bengaluru Metro city. Using a quantitative approach with a cross-sectional design, data was collected through a self-structured questionnaire comprising 20 Likert scale statements. Results indicate that influencers significantly increase the awareness of health and fitness products among Millennials, with trust in their recommendations playing a crucial role in shaping purchasing decisions. The study also reveals that the perceived authenticity of influencer endorsements impacts consumer perceptions of brands in the health and fitness sector. Moreover, age and fitness levels influence the effectiveness of influencer marketing, with older individuals and those at higher fitness levels generally showing stronger responses to influencer endorsements. Studies highlight the growing role of digital platforms in consumer engagement and the evolving dynamics of influencer-consumer relationships in India. By understanding the preferences and behaviors of Millennial consumers, brands can effectively leverage influencer partnerships to foster authenticity and trust, ultimately driving engagement and enhancing brand perception in the digital age. This study contributes to the existing body of knowledge by offering empirical insights into how influencer marketing influences consumer behavior in the health and fitness industry, specifically among Millennials in India. Future research could explore longitudinal effects and delve deeper into the cultural differences shaping consumer responses to influencer endorsements.